Managing Wildfire for Whitebark Pine Ecosystem Restoration in western North America - Keane, Robert E. (Forests, 2018)
Wildfire in declining whitebark pine forests can be a tool for ecosystem restoration or an ecologically harmful event. This document presents a set of possible wildfire management practices for facilitating the restoration of whitebark pine across its range in Western North America. These management actions are designed to enhance whitebark pine resilience and health, while also being effective wildfire management measures. The actions are presented by the three phases of the wildfire continuum: Before, during, and after a wildfire. Current pre-wildfire restoration actions, such as mechanical thinning’s, prescribed burning, and fuel treatments, can also be designed to be fuel treatment activities that allow more effective suppression of wildfires when needed. Three wildfire strategies can be implemented while the wildfire is burning—full suppression, partial suppression, and wildland fire use (letting some fires burn under acceptable conditions)—for protecting valuable whitebark pine trees and for ecosystem restoration. Finally, post-wildfire activities include planting rust-resistant seedlings and monitoring effects of the wildfires. Recommended wildfire management practices for the wildfire continuum are specified by region, site type, and stand type in the last section of this paper.